UV- SPECTROPHOTOMETRIC METHOD DEVELOPMENT AND VALIDATION FOR ESTIMATION OF STRONTIUM RANELATE IN BULK - A.S. SWAMI; S.A. PISHAWIKAR; H.N. MORE (International Journal of Pharma and Bio Sciences, 2012)
Strontium ranelate is used for treatment of osteoporosis. The present work deals with method development for estimation of Strontium ranelate in bulk dosage form by UV spectrophotometry. A new simple, accurate and sensitive method for estimation of Strontium ranelate from bulk dosage form has been developed. The method employs zero order derivative spectroscopy. Estimation of Strontium ranelate was done in zero order derivative mode at 323 nm and obeyed Beer’s law in the range of 4-28 μg/ml . The results of analysis were validated statistically as per ICH guidelines and recovery studies showed satisfactory results. Thus the method is accurate and reproducible and can be employed for routine analysis of the drug from bulk dosage forms.